Kanserden sağ kalanlarda erişkin yaşam kalitesi ölçeğinin Türkçe geçerlilik ve güvenirliği - KOLAÇ, NURCAN (My University, 2022)
Gereç ve Yöntemler: Metodolojik tasarıma sahip araştırma, üç yıl ve üzeri kanser tanısı olan hastalar ile yürütülmüştür. Veri toplamak için; “Tanıtıcı Bilgi formu” ve “Kanserden Sağ Kalanlarda Erişkin Yaşam Kalitesi Ölçeği” (Quality of Life in Adult Cancer Survivors =QLACS) kullanılmıştır. Çalışmada ölçeğin dil ve kapsam geçerliği, yapı geçerliği, güvenirlik değerlerini belirleme aşamaları sırasıyla gerçekleştirilmiştir. Bulgular: Yapılan kapsam geçerliğinde ölçek maddelerine ilişkin uzman görüşleri arasında yüksek derecede uyum olduğu saptanmıştır (KGİ=0.88). Açımlayıcı faktör analizi sonucunda, ölçeğin toplam varyansın %91.4’ünü açıklayan 11 faktörlü yapıya sahip olduğu belirlenmiştir. Doğrulayıcı faktör analizi sonucunda elde edilen modelin kabul edilebilir uyum indeksi sınırlarında ve faktör yüklerinin 0.867-0.966 arasında olduğu saptanmıştır. Ölçeğin alt boyutlarının Cronbach alfa güvenirlik katsayısı 0.867-0.966 olarak belirlenmiştir. Sonuçlar: Kanserden Sağ Kalanlarda Erişkin Yaşam Kalitesi Ölçeğinin Türkçe versiyonunun üç yıl ve üzeri kanser hastalarında genel ve kansere özgü yaşamlarını değerlendiren, geçerli ve güvenilir bir araç olduğu saptanmıştır.

Objectives: The aim of this study is to conduct the Turkish validity and reliability study of the Adult Life Quality Scale in Cancer Survivors. Materials and Methods: The research with a methodological design was carried out with patients diagnosed with cancer of three years or more. To collect data; “Introductory Information Form”, Adult Life Quality Scale of Cancer Survivors (QLACS) was used. In the study, the language and content validity, construct validity, and reliability determination steps of the scale were carried out respectively. Results: In the validity of the scope, there was a high degree of agreement between the opinions of the experts on the scale items (KGI=0.88). As a result of the exploratory factor analysis, it was determined that the scale has an 11-factor structure that explains 91.4% of the total variance. Confirmatory factor analysis revealed that the model obtained was within the acceptable fit index limits and factor loadings were between 0.867-0.966. Cronbach alpha reliability coefficient of the sub-dimensions of the scale was determined as 0.867-0.966. Conclusions: The Turkish version of the Adult Quality of Life Scale for Survivors of Cancer has been found to be a valid and reliable tool that evaluates general and cancer-specific lives in cancer patients over three years
Turkish validity and reliability of adult life quality scale in cancer survivors
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Cancer; Quality of life; Reliability; Survival; Validity; Geçerlik; Güvenirlik; Kanser; Sağkalım; Yaşam kalitesi